A review of nature and scope of financial economics - Devi, Sunita (Innovative Research Thoughts, 2017)
The overall degree of optimism/pessimism in society is represented by the emotions of financial decision-makers. “Our hypothesis leads to three significant results due to the correlation between these feelings and economic actors. First, social mood impacts the sorts of choices made by customers, investors, and business management equally. Optimistic (pessimistic) collective investment and corporate activity are indicators of societal mood swings. Second, owing to the efficient and emotive character of stock transactions, the stock market itself is a direct indicator or barometer of societal mood. Third, stock market patterns assist foretell future financial and economic activity because the tone and nature of corporate activity follows rather than leads societal mood. Detailed forecasts are provided for the future of the stock market and trading volume, market volatility, company growth, leverage use, initial public offerings, and mergers and acquisitions.